Electrochemotherapy in Skin Malignancies of Head and Neck Cancer Patients: Clinical Efficacy and Aesthetic Benefits - Antonio Bonadies; Ettore Bertozzi; Renzo Cristiani; Flavio A. Govoni; Emilia Migliano (Medical Journals Sweden, 2019)
Skin malignancies of the head and neck inflict significant structural, functional, and cosmetic burdens upon those affected. We retrospectively addressed electrochemotherapy anti-tumour efficacy in head and neck skin cancer patients who were not suitable for standard treatments. Scars' physical characteristics and aesthetics were evaluated using validated scar assessment scales. Among 33 treated patients, 82% experienced a complete tumour response while 18% experienced a partial response. At a median time period of 7 months, 96% of the evaluated scars came close to resembling the normal surrounding skin showing excellent results in terms of restoration to original condition with no deformity and/or distortion and in terms of preservation of functionality, such as oral competence and eye protection. Electrochemotherapy is an effective local anticancer procedure for cutaneous tumours. In the treatment of skin malignancies of the head and neck, especially in non-surgical cases, in the elderly and in patients declining surgery, electrochemotherapy may represent a valid alternative to standard management.